Քրիստոսի Սուրբ Գերեզմանում հայոց պատարագի իրաւունքի վերականգնումը 1829 թ. թագաւորական հրովարտակով - Յակոբեան, Տ. Տիրան աբղյ. (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
После многих трудностей и страданий, благодаря усилиям архимандрита Закарии Кобеци, арх. Погос Адрианополсеци, Микаэла Бишмишяна и Арутюна Безджяна армянам удалось убедить султана Махмуда II издать в 1829 году прокламацию/указ, в котором подтверждалось право армян на богослужение в Храме Святого Воскресения. Это событие доставило великую радость армянам всего мира. Братство Свв. Иаковов и Армянский Патриархат Иерусалима взяли на себя эту пожизненную миссию и по сей день отстаивают данное важнейшее право ежедневными богослуженими в Храме Святого Воскресения. After countless struggles and suff erings, thanks to the eff orts of Archimandrite Zachariah Kobetsi, Archbishop Poghos of Adrianople, Michael Bishmishian and Harutyun Bezdjian, the Armenians convinced Sultan Mahmud II to issue a decree in 1829 affi rming the right of the Armenians to hold services in the Church of the Holy Sepulchre, which brought great joy to all the Armenians around the world. The Brotherhood of Sts. James and the Armenian Patriarchate of Jerusalem, through their daily services in the Church of the Holy Sepulchre, have upheld this most important right to this day as a lifelong mission.
Keywords: Կրօնագիտական